Wear and airborne noise interdependency at asperitical level: analytical modelling and experimental validation - Lontin, Kevin; Khan, Muhammad A. (MDPI, 2021)
Generation of wear and airborne sound is inevitable during friction processes. Previously, the relationship between the wear and the sound has only been determined experimentally. Analytical models do exist, but they remain rare and do not fully account for the wear and the airborne sound generation especially at the asperitical level. This model attempts to fill the gap by providing a quantifiable relationship at an asperitical level between the wear generated and the sound emitted in a simple pin-on-disc setup. The model was validated for three materials (iron, mild steel, and aluminium T351) under two loads (10 N and 20 N) at 300 RPM. The theoretical model agrees with the experimental results with a varying error of 10 to 15% error in iron and aluminium. However, a larger error is observed in the case of mild steel. The model could be refined to improve the accuracy as it assumes point impacts on the asperities where a distributed impact would be more suitable. Furthermore, the pin is assumed a single asperity to simplify the model at the expense of accuracy. Overall, the experimental results are in good correlation with the theoretical results and this model provides the first step in quantifying wear using only the recorded sound pressure.
Keywords: friction; wear; airborne noise; asperities; analytical model